Fraud Prevention Mechanism: Enhancing From Religiosity, Whistleblowing Protection, and Whistleblowing Intention - - Prasetyono; - Tarjo; Elita Aprilianty; Ach Fawaid As'ad; Indra Prayitno; Erfan Muhammad; Emi Rahmawati (Universitas Trunojoyo Madura, 2021)
This study aims to determine fraud prevention from the perspective of religiosity, whistleblower protection, and Whistleblowing Intention. This research was conducted on PT Asuransi Prudential Life employees with a sampling technique of census (saturated sample) totalling 37 people. Data collection in this study was carried out by distributing questionnaires to respondents and testing the research hypothesis using multiple linear regression analysis. The results of the study show that religiosity and whistleblowing protection does not affect fraud prevention. The results of this study indicate that the religious values of employees are not internalized in attitudes and behaviour to prevent fraud, namely by working well and professionally and reporting fraudulent acts in the company. In addition, the findings of this research also indicate that the protection for whistleblowers in the company does not encourage (attract) employees to prevent fraud by reporting fraud because of the negative impact it will receive. The results also show that whistleblowing intention has a significant and positive effect on fraud prevention, indicating that employees have the intention and desire to report fraudulent actions to prevent fraud that can harm the company.